2010
DOI: 10.3846/transport.2010.07
|View full text |Cite
|
Sign up to set email alerts
|

Designing Container Shipping Network Under Changing Demand and Freight Rates

Abstract: Abstract. is paper focuses on the optimization of container shipping network and its operations under changing cargo demand and freight rates. e problem is formulated as a mixed integer non-linear programming problem (MINP) with an objective of maximizing the average unit ship-slot pro t at three stages using analytical methodology.e issues such as empty container repositioning, ship-slot allocating, ship sizing, and container con guration are simultaneously considered based on a series of the matrices of dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In particular, they observed that although the average shipping cost per twenty-foot equivalent unit (TEU) decreased on line-haul legs of hub-and-spoke networks, freight originating in feeder ports via smaller feeder ships could incur extra shipping distance, shipping time, and port charges. Extending the work of Hsu and Hsieh (2007), Chen and Zeng (2010) proposed a mixed-integer non-linear program that could simultaneously determine empty container repositioning, ship-slot allocating, ship sizing, and container configuration based on a series of changing demand and freight rates. None of these earlier models, however, was designed to assess the impact of vessel size on the port charge.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they observed that although the average shipping cost per twenty-foot equivalent unit (TEU) decreased on line-haul legs of hub-and-spoke networks, freight originating in feeder ports via smaller feeder ships could incur extra shipping distance, shipping time, and port charges. Extending the work of Hsu and Hsieh (2007), Chen and Zeng (2010) proposed a mixed-integer non-linear program that could simultaneously determine empty container repositioning, ship-slot allocating, ship sizing, and container configuration based on a series of changing demand and freight rates. None of these earlier models, however, was designed to assess the impact of vessel size on the port charge.…”
Section: Prior Literaturementioning
confidence: 99%
“…These attempts include Ryder and Chappell (1980), Min and Guo (2004), Hsu and Hsieh (2007), and Chen and Zeng (2010). To elaborate, Ryder and Chappell (1980) investigated how vessel size and speed influenced the deep-sea cargo liner's length of stay at the port and developed a mathematical model to determine an optimal vessel size and speed that could maximize the cargo liner's profit subject to constraints of service frequency and limited cargo demand.…”
Section: Prior Literaturementioning
confidence: 99%
“…They pointed out that with a slight modification, their model can optimize the slot allocation of empty containers as well. Chen and Zeng (2010) presented a more comprehensive model to optimize shipping route and slot allocation for full and empty containers simultaneously.…”
Section: I T E R a T U Re R Ev I Ewmentioning
confidence: 99%
“…In such an operational environment, decisions must be made not only concerning ship scheduling and cargo distribution but also on how to employ port facilities to full capacity, when and how to upgrade facilities, a schedule of repair and maintenance works and plan work shi s. Such decisions are o en inuenced by the events that cannot be predicted with certainty. e major objective of planning port operations is to diminish port vacancy, thus minimizing operational costs while assuring that service rendered to ships is in line with widely accepted standards (Česnauskis 2007;Hsu and Hsieh 2007;Jaržemskis and Vasilis Vasiliauskas 2007;Afandizadeh and Moayedfar 2008;Paulauskas and Bentzen 2008;Vasilis Vasiliauskas and Barysienė 2008;Imai et al 2009;Liu et al 2009;Su and Wang 2009;Chen and Zeng 2010).…”
Section: Introductionmentioning
confidence: 99%